1982
DOI: 10.1021/je00028a027
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of cuprous chloride in various soluble aqueous chlorides

Abstract: Smoothed tables of the odubiHty of CuCl In aqueous HCI and aqueous NaCi from 0.01 to 6.0 M and from 0 to 100 OC are presented. Similar tables are given, for 25 OC only, for mixtures of HCI and NaCI, and for solutions In aqueous KCI, NH,Ci, CuCI,, and Feci,. The procedures and parameters necessary for calculation of the solubility at other concentrations and temperatures are given. Slmple methods for handling solublitty in complex mlxtures and in cases where experimental Information Is scant are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…S1, ESI †), which are not suitable templates for the hollow Cu 2 O nanocubes. 3,28 Based on the analysis above, the formation of the reaction intermediate CuCl ought to be a key procedure in the fabrication of hollow Cu 2 O nanocubes. In order to nd out possible template for hollow Cu 2 O nanocubes, we surveyed all the copper compounds possibly formed in our synthetic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…S1, ESI †), which are not suitable templates for the hollow Cu 2 O nanocubes. 3,28 Based on the analysis above, the formation of the reaction intermediate CuCl ought to be a key procedure in the fabrication of hollow Cu 2 O nanocubes. In order to nd out possible template for hollow Cu 2 O nanocubes, we surveyed all the copper compounds possibly formed in our synthetic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal sizes of chloro complexes and conversion rates from CuCl to CuCl2 have been reported by O'Connor et al [26]. Experiments were performed by Fritz [27] to determine the solubility of copper (I) chloride in various aqueous chlorides and their associated equilibrium constants of formation. It was found that a set of viral parameters representing the activity coefficients of the ions formed in dissolution.…”
Section: Introductionmentioning
confidence: 93%
“…[21] At the same time, as the H + and Cl − were produced, the CuO nanocube template was gradually dissolved into aqueous solution under an acidic environment in the present of Cl − , forming [CuCl x ] 1−x . [24][25][26] In turn, the consumption of H + and Cl − can further accelerate the hydrolysis of Fe 2+ in the current reaction system. Under this case, even though the concentration of Fe 2+ is not high for homogeneous nucleation, the precursor (FeOOH) of Fe 2 O 3 could heterogeneously nucleate at the interface and the vacancy within FeOOH generates originating from the complete consumption of inner CuO nanocubes, leading to formation of hierarchical FeOOH Li-ion batteries have already dominated the portable electronics market and are now expanding their territory into large scale electric energy storage applications such as in electric vehicles and renewable power stations.…”
Section: Doi: 101002/aenm201600256mentioning
confidence: 99%